Effect of recombinant PDGF-BB on bone formation in the presence of ß-tricalcium phosphate and bovine bone mineral matrix: A pilot study in rat calvarial defects - Luvizuto, Eloá R. [UNESP] (2016)
Background: Supplementation of bone substitutes with recombinant platelet-derived growth factor-BB (PDGF-BB) can enhance bone regeneration. The aim of the study was to evaluate the effect of PDGF-BB on bone formation in the presence of ß-tricalcium phosphate and bovine bone mineral matrix in a rat calvaria defect model. Methods: The authors examined 5 mm rat calvarial defects treated with ß-tricalcium phosphate (TCP) or demineralized bovine bone mineral (DBBM) with and without 0.3 mg/ml recombinant PDGF-BB. Calvaria defects were randomly divided into the following treatment groups (n = 5); TCP; TCP plus PDGF-BB; DBBM; DBBM plus PDGF-BB; and untreated empty control. After 45 days, bone formation was evaluated by histomorphometry and fluorescence microscopy. Results: The authors report that the area of newly formed bone was similar between the empty controls and the two bone substitutes, TCP and DBBM. Supplementation of TCP and DBBM with PDGF-BB had no significant impact on bone formation. Fluorochrome staining revealed no visible changes in the pattern of bone formation in defects filled with TCP and DBBM, irrespective of PDGF-BB. Furthermore, supplementation with PDGF-BB did not influence biomaterial degradation. Conclusions: The authors concluded that PDGF-BB had no impact on bone formation and degradation of bone substitutes in the respective rodent models. Thus, possible beneficial effects of PDGF-BB may require other model situations.